2007
DOI: 10.1063/1.2773947
|View full text |Cite
|
Sign up to set email alerts
|

Energy relaxation of InN thin films

Abstract: The energy relaxation of InN thin films has been studied by ultrafast time-resolved photoluminescence technique. The obtained carrier cooling curves can be explained by carriers releasing excessive energy through the carrier–LO-phonon interaction. The extracted effective phonon emission times decrease as the photoexcited carrier concentration reduces and come close to the theoretical prediction of 23fs at small carrier concentration. The reduction of energy loss rate at high photoexcited carrier density is att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Table 2 summarizes the material parameters of wurtzite InN used in the simulations. The model of InN yields the electron-optical phonon emission time t e ¼ 29 fs for the photon energy of 1.53 eV and at a temperature of 35 K. This value of t e is in agreement with the experimental value t e ¼ 23-31 fs [14] obtained at the same conditions and at small carrier concentration at which the hot phonon effects are weak.…”
Section: Model Of Innsupporting
confidence: 80%
“…Table 2 summarizes the material parameters of wurtzite InN used in the simulations. The model of InN yields the electron-optical phonon emission time t e ¼ 29 fs for the photon energy of 1.53 eV and at a temperature of 35 K. This value of t e is in agreement with the experimental value t e ¼ 23-31 fs [14] obtained at the same conditions and at small carrier concentration at which the hot phonon effects are weak.…”
Section: Model Of Innsupporting
confidence: 80%
“…Jang et al proposed the suppression of electron energy relaxation by a hot phonon effect and denied the possibility of Coulomb screening of the LO phonon interaction. 89) On the other hand, Su et al attributed the dependence of the relaxation rate on the carrier density to the screening effect, 90) and Tsai et al ascribed it to the hot electron effect. 91) Yang et al proposed the contribution of piezoelectronic coupling to acoustic phonons.…”
Section: ¹1mentioning
confidence: 99%
“…Much studies on the physical and optical properties of this alloy have been reported. However, carrier dynamics and the related material characteristics such as the recombination lifetime and the carrier thermalization have been reported for InN only [5,6]. In this paper, we investigate the optical properties of InGaN epilayers with different gallium fractions using time-resolved photoluminescence (TRPL) and report the hot carrier relaxation characteristics for In 0.83 Ga 0.17 N layer.…”
mentioning
confidence: 97%